CINEMATIC ACTS OF RESISTANCE: FEMINIST RE-IMAGININGS OF CARE WORK IN GULZAR'S AANDHI AND IJAAZAT - Bhowmik, Niharika; Mallik, Pradeep; Mahajan, Sandesh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This paper conducts a scene-by-scene qualitative study of two films by Gulzar, Aandhi (1975) and Ijaazat (1987), and explores the transformation of the emotional and care labour of women into patriarchal resistance acts. Based on feminist film theory (Mulvey and Smelik) and emotional labour framework by Hochschild, this paper discusses how the characters, Aarti Devi and Sudha, utilise caregiving, silence, presence and withdrawal to assert their agency in environments which devalue the emotional and relational labour of women. The findings of the close textual analysis and coding of themes testify that care work in these films is not blind obedience but deliberate feminist actions. The two characters convert domestic and emotional labour to self-preservation and dignity as they negotiate their visibility and withdrawal as means of managing patriarchal control and male gaze. The paper also demonstrates how the use of emotional labour can be politically significant when executed consciously and reflectively so that apparently accommodative gestures can serve as instances of ethical and narrative power. By extending Mulvey's concept of the gaze beyond scopophilia and Hochschild's emotional labour theory within South Asian cinematic contexts, this research positions care and emotional labour as culturally specific forms of feminist agency. Thus, it contributes to transnational feminist film studies by foregrounding "quiet feminism" as an important form of resistance beyond Western models that privilege vocal or spectacular opposition.